Avaliação da influência de medicamentos homeopáticos com tropismo ósseo sobre células-tronco mesenquimais da polpa de dente decíduo - Pereira, Marli Cristina (2020)
Homeopathy consists of drug therapy that uses its own methods to fully interpret and treat the patient. Tropism medication is one that has in its pathogenesis characteristics similar to the patient's site or tissue, due to its electivity. The objective of this work was to investigate the influence of homeopathic medicines (MH) with bone tropism, in the culture of stem cells from human exfoliated deciduous teeth (SHED). The homeopathic medicines Calcarea carbonica (CC), Calcarea phosphorica (CP) and Symphytum officinale (SO) were tested, all in potency 30 CH; administered daily in wells containing SHED, cells validated in the Dominici Protocol and already plated. In the negative control (C-) ultrapure water by reverse osmosis was used in the wells containing SHED, while in the positive control (C +) the conventional culture medium (DMEM) was used. The 3 MH were subjected to tests of 24, 48 and 72 hours. All assays were performed in biological duplicate (from the same sample, cells in different subcultures or passages, P4 and P5), and in triplicate (n = 3) for each pass. The following cell assays were used: viability (Neutral Red), cytotoxicity (MTT) and proliferation (Crystal Violet). Statistical analysis was performed with α = 0.05 (SPSS Statistics). In P4, in the 72 h final time, the CP and SO groups showed the highest cell viability; while in P5 there were no differences among groups. In the proliferation assay, in P4, the CC and SO groups had the lowest total averages (among 24, 48 and 72 h); in P5, C+ showed the highest cell proliferation in 72 h, while the other groups showed no differences among them. As for cytotoxicity in P4, the SO presented the highest cytotoxicity in 24 h, in 48 h it was similar to the others with the exception of C +, and in 72 h presented cytotoxicity similar to C-. In P5, SO demonstrated the highest cytotoxicity only at 72 h. At Scanning Electron Microscopy (SEM), the SO showed an aspect of ultramorphology suggestive of a greater number of cells than the C +, with cells adhered and spread, confluent and in close association, without cell death. Further research was suggested, including the osteoinduction test, and the immunofluorescence test to detect specific bone molecules possibly secreted to the extracellular matrix. It can be concluded that the concentrations and potency of the tested MH influenced the cultivation of stem cells, without significant negative effects, suggesting new studies based on the same conditions.